PERAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM PEMANFAATAN INTERNET: STUDI KASUS DI DESA BABAKAN PEUTEUY, KECAMATAN CICALENGKA KABUPATEN BANDUNG - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The purpose of this research is to optimize the role of MSMEs through the use of the internet as a media of promotion for local economic potential in the Babakan Peuteuy Village, Cicalengka District, Bandung Regency, namely the business of bamboo craftsmen, campsite attractions, tofu and tempeh and veil products by using the website as a medium promotion for various products in the Village of Babakan Peuteuy. The method implemented is through surveys and descriptive analysis. The results of the analysis show that the local economic potential in Babakan Peuteuy village is quite good and creative, and the desire of citizens to carry out entrepreneurial activities is already high, but there are still many problems such as an unprofessional organizational structure, poor business management, the technology used is mostly still traditional , raw materials originating from outside the village, lack of human resources, and an inability to market products online. Therefore, together with village officials have tried to make a website. The existence of the use of internet media information dissemination will be faster and wider reach in increasing sales and marketing of products.